PENGARUH EARNING PER SHARE DAN DIVIDEND PER SHARE TERHADAP HARGA SAHAM PADA BANK RIAU KEPRI KOTA BATAM - Jurnal Akuntansi Barelang (LPPM Universitas Putera Batam, 2017)
The purposive of this study to determine the influence of earning per share and dividend per share to stock price at Bank Riau Kepri Batam city. The data used this research is secondary data such as monthly financial statement Bank Riau Kepri Batam city for a period of five years from 2011 to 2015. The method of analys in this study using multiple linier regression. The result showed that the partial of earning per share and significant negative effect on stock price of 0,019 and dividend per share no significant on stock price of 0,234. Simultaneously, earning per share and dividend per share significantly positif on stock price. Rated R Square of 11.4%. this shows the value of variable earning per share and dividend per share are able to explain the stock price amounted to 11.4%.